2016
DOI: 10.1152/ajprenal.00082.2015
|View full text |Cite
|
Sign up to set email alerts
|

Paricalcitol modulates ACE2 shedding and renal ADAM17 in NOD mice beyond proteinuria

Abstract: -Circulating and renal activity of angiotensin-converting enzyme 2 (ACE2) is increased in non-obese diabetic (NOD) mice. Because paricalcitol has been reported to protect against diabetic nephropathy, we investigated the role of paricalcitol in modulating ACE2 in these mice. In addition, renal ADAM17, a metalloprotease implied in ACE2 shedding, was assessed. NOD female and non-diabetic control mice were studied for 21 days after diabetes onset and divided into various treatment groups. Diabetic animals receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 54 publications
2
61
0
Order By: Relevance
“…ADAM17 is abundant in different organs and cleaves several cell surface enzymes, including ACE2 and NEP (8,16,23,36,38,41,54). We detected increased urinary ADAM17 in all patients with diabetes, including Dnormo.…”
Section: Discussionmentioning
confidence: 70%
“…ADAM17 is abundant in different organs and cleaves several cell surface enzymes, including ACE2 and NEP (8,16,23,36,38,41,54). We detected increased urinary ADAM17 in all patients with diabetes, including Dnormo.…”
Section: Discussionmentioning
confidence: 70%
“…In addition, DIZE treatment reduced the mRNA expression of ACE in whole kidney and increased the mRNA expression of ACE2 in glomeruli of diabetic animals, whereas adding PD123319 had no effect on these actions of DIZE (Figure A, B, F, G). Recent studies have demonstrated that the increased urinary levels of ACE2 and activity in animal models of DN were due to increased activity of ADAM17 and that inhibition of ADAM17 reduced urinary ACE2 levels and activity (Salem et al ., ; Riera et al ., ). In our study, DIZE significantly reduced levels of urinary ACE2, whereas DIZE combined with PD123319 lost this effect to some extent and resulted in increased urinary ACE2 levels (Figure A).…”
Section: Discussionmentioning
confidence: 97%
“…With regard to protein expression, ACE2 expression levels were increased in lungs and heart at early stage of diabetes and in pancreas at late stage of diabetes. Previous studies postulated that the differences observed in ACE2 activities are related to ADAM17 sheddase activity [41]. However, no differences were found when studying ACE2 and ADAM17 activities and gene expression in pancreas islet from db / db mice as compared to the respective db / m controls [42].…”
Section: Discussionmentioning
confidence: 99%